A note on irrationality measures - Hancl, Jaroslav; Stepnicka, Jan (Mathematica Scandinavica, 2009)
The paper deals with lower estimates for the irrationality measure of the sum of a special series. The result depends only on the form of convergence and does not make use of divisibility properties of integers or any algebraic identities.